2014
DOI: 10.5713/ajas.2013.13604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forage Sources on Rumen Fermentation Characteristics, Performance, and Microbial Protein Synthesis in Midlactation Cows

Abstract: Eight multiparous Holstein cows (632±12 kg BW; 135±16 DIM) were used in a replicated 4×4 Latin square design to evaluate the effects of forage sources on rumen fermentation characteristics, performance, and microbial protein (MCP) synthesis. The forage portion of the diets contained alfalfa hay (AH), oat hay (OH), Leymus chinensis (LC), or rice straw (RS) as the primary source of fiber. Diets were isonitrogenous and isocaloric, and cows were fed four corn silages based total mixed rations with equivalent nonfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(35 reference statements)
7
10
0
4
Order By: Relevance
“…The incorporation of water spinach as the source of fiber in the pelleted feed did not impact the pH, ammonia, enzyme protein and microbial protein. This finding was in accordance with a study conducted by Al-Arif et al (2017); Li et al (2003); Xu et al (2014). Zhang et al (2019) reported that rumen pH is highly dependent on feed fermentation and its physical form.…”
Section: Discussionsupporting
confidence: 92%
“…The incorporation of water spinach as the source of fiber in the pelleted feed did not impact the pH, ammonia, enzyme protein and microbial protein. This finding was in accordance with a study conducted by Al-Arif et al (2017); Li et al (2003); Xu et al (2014). Zhang et al (2019) reported that rumen pH is highly dependent on feed fermentation and its physical form.…”
Section: Discussionsupporting
confidence: 92%
“…; Xu et al . ). After obtaining approximately 200 mL of rumen fluid the pH was immediately measured (Model HI 98127 Waterproof pH meter; Fotronic Corporation).…”
Section: Methodsmentioning
confidence: 97%
“…The tubing and probe head were inserted into the rumen at a depth of 180 cm followed by 200 cm for collection. To ensure minimal saliva contamination the first 200 mL of rumen fluid extracted was discarded (Shen et al 2012;Xu et al 2014). After obtaining approximately 200 mL of rumen fluid the pH was immediately measured (Model HI 98127 Waterproof pH meter; Fotronic Corporation).…”
Section: Ruminal Fluid Analysismentioning
confidence: 99%
“…Among the various lines of research related to ruminant nutrition, the study of the relationship between NDF and NFC is of great importance. Suitable NDF levels in a ruminant's diet during production are usually adjusted in order to maintain normal function of the rumen, maintain microbial protein synthesis (Xu et al, 2014), and optimize its intake and digestibility (Oliveira et al, 2011). Similarly, the NFC content has been considered in ruminant ration formulations as a nutritional criterion that is adjusted to obtain the appropriate fiber fraction in the feed (NRC, 2001).…”
Section: Introductionmentioning
confidence: 99%